Growth performances of freshwater prawn Macrobrachium rosenbergii (De man) in an integrated farming system. - Idris, Mohd Hanafi; Mohd Ali, Mohd Aliff; Gayah, Jackson; Hassan, Mohd Zafri; Zainal Abidin, Aizam (INSInet Publication, 2011)
The growth performances of giant Malaysia prawn (Macrobrachium rosenbergii) in different compartments of an integrated culture system were evaluated during 12 weeks culture period. Macrobrachium rosenbergii were placed in tanks at about 150 individuals per tank. The experiment divided into five treatments and control tank with three replicates. Result on growth performance of M. rosenbergii shows the growth relative rate, final length and final weight differed significantly (p<0.05) between treatment. For the length-weight relationship, the growth coefficient (b) of M. rosenbergii was ranged between 2.37 to 3.38 at 95% confidence limit which concentration with 20 g recorded the higher value and the lower was recorded by the concentration of 40 g. The regression between length and weight showed a positive relationship which r 2 values ranged of 0.89 to 0.99. No significant difference (p>0.05) was observed during the study period on high, leaf width and weight of vegetables. In an integrated culture system, both Malaysian prawns and vegetables grow well in this system.